2012
DOI: 10.1074/jbc.m112.368712
|View full text |Cite
|
Sign up to set email alerts
|

Generation of N-Acylphosphatidylethanolamine by Members of the Phospholipase A/Acyltransferase (PLA/AT) Family

Abstract: Background:The mammalian enzymes that form N-acylphosphatidylethanolamines (NAPEs), precursors of bioactive N-acylethanolamines, are poorly understood. Results: PLA/AT family proteins, previously known as tumor suppressors, catalyzed N-acylation of phosphatidylethanolamine, and their overexpression in animal cells remarkably increased endogenous levels of NAPEs. Conclusion: These proteins may function as NAPE-forming enzymes in vivo. Significance: Our results may contribute to a better understanding of the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 42 publications
2
72
0
1
Order By: Relevance
“…Previously, we suggested that the overexpression of PLA/ AT-2 (HRASLS2) also causes the dysfunction of peroxisomes (28), whereas PLA/AT-1 (HRASLS1, A-C1) did not appear to affect peroxisomal functions (45). In the present study, we observed that PLA/AT-2 inhibited the binding of Pex19p to Pex3p and Pex11␤p and decreased the protein level of PMP70.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Previously, we suggested that the overexpression of PLA/ AT-2 (HRASLS2) also causes the dysfunction of peroxisomes (28), whereas PLA/AT-1 (HRASLS1, A-C1) did not appear to affect peroxisomal functions (45). In the present study, we observed that PLA/AT-2 inhibited the binding of Pex19p to Pex3p and Pex11␤p and decreased the protein level of PMP70.…”
Section: Discussionsupporting
confidence: 63%
“…Thus, we proposed to rename HRASLS1 to 5 as phospholipase/acyltransferase-1 to -5 (PLA/AT-1 to -5), respectively (26). Unexpectedly, we found that the overexpression of PLA/AT-3 (HRASLS3, H-rev107, or AdPLA) or PLA/ AT-2 (HRASLS2) in mammalian cells results in the disappearance of peroxisome membrane structure and the dysfunction of peroxisomes, as revealed by a remarkable decrease in the intracellular levels of ether-type lipids (27,28). The disappearance of peroxisomes was dependent on the enzyme activity of PLA/ AT-3 because the mutant devoid of enzyme activity failed to affect peroxisome functions (27).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…34,35 In addition, RARRES3 has recently been shown to display phospholipase PLA 1/2 and acyltransferase activities in in vivo and in vitro studies. 36,37 Furthermore, previous studies on the tumorsuppressive effect of RARRES3 focused primarily on the characterization of its functional domains and its physiological targets, while few reports have investigated the implications of its enzymatic activity. Because acylation of signaling proteins is important for the maintenance of cell physiological responses, it is assumed that the enzymatic activity of RARRES3 may be closely linked to its tumorsuppressive effect.…”
mentioning
confidence: 99%
“…[1,[2][3][4][5][6][7][8][9][10][11][12][13][14] C]ethanolamine HCl was from Moravek Biochemicals (Brea, CA). Horseradish peroxidaselinked anti-mouse and anti-rabbit IgGs were from GE Healthcare (Piscataway, NJ).…”
Section: 2-[1′-mentioning
confidence: 99%